Composited reduced graphene oxide into LiFePO4/Li2SiO3 and its electrochemical impedance spectroscopy properties. (23rd March 2017) - Arifin, M; Rus, Y B; Aimon, A H; Iskandar, F; Winata, T; Abdullah, M; Khairurrijal, K
Abstract: LiFePO4 is commonly used as cathode material for Li-ion batteries due to its stable operational voltage and high specific capacity. However, it suffers from certain disadvantages such as low intrinsic electronic conductivity and low ionic diffusion. This study was conducted to analyse the effect of reduced graphene oxide (rGO) on the electrochemical properties of LiFePO4 /Li2 SiO3 composite. This composite was synthesized by a hydrothermal method. Fourier transform infrared spectroscopy measurement identified the O–P–O, Fe–O, P–O, and O–Si–O − bands in the LiFePO4 /Li2 SiO3 composite. X-ray diffraction measurement confirmed the formation of LiFePO4 . Meanwhile, Raman spectroscopy confirmed the number of rGO layers. Further, scanning electron microscopy images showed that rGO was distributed around the LiFePO4 /Li2 SiO3 particles. Finally, the electrochemical impedance spectroscopy results showed that the addition of 1 wt% of rGO to the LiFePO4 /Li2 SiO3 composite reduced charge transfer resistance. It may be concluded that the addition of 1 wt% rGO to LiFePO4 /Li2 SiO3 composite can enhance its electrochemical performance as a cathode material.